Biological matrices for determining the origin of post-mortem ethanol: Recommendations for collection and storage - Allane Patricia Santos da Paz; Luiz Basílio Bouzas Nunez; Vanessa Jóia de Mello (International Journal of Legal Medicine, 2026)
Abstract Ethanol is one of the most widely used psychoactive substances worldwide and one of the most frequently investigated substances in forensic toxicology laboratories. Choosing the most appropriate biological sample for its screening is extremely important in forensic autopsy, mainly to differentiate alcohol consumed before death from alcohol formed post-mortem , as well as to reduce the risk of ethanol loss through oxidation or metabolism. Therefore, this study presents an integrative review of recent literature on the collection, storage, and availability of biological matrices collected during forensic autopsy for detecting alcohol and its metabolites, considering the post-mortem condition and decomposition status of the body. The Scopus, Web of Science, and PubMed databases were searched, with searches limited to English-language articles from the past 10 years, excluding reviews and meta-analyses. The language and time restrictions were adopted to ensure methodological consistency, linguistic homogeneity, accessibility for an international readership, and focus on recent evidence relevant to current forensic toxicology practice. After excluding duplicates, the initial screening identified 414 articles. After analyzing the titles, abstracts, and full texts, articles with unavailable full text, incorrect study design, incorrect publication type, or off-topic content were excluded. From a detailed analysis of the 54 definitively included articles, data were collected on study objectives, main results, recommendations for collection and storage, and potential biomarkers. In general, it is recommended to analyze multiple matrix types and biomarkers, collect samples in duplicate, refrigerate or freeze them depending on the storage time, use preservatives, and provide adequate staff training. Protocols that provide greater clarity between results and more faithfully reflect real conditions are relevant to investigations and can prevent or detect alterations in ethanol levels in biological samples, thereby ensuring the validity, integrity, and traceability of evidence from its collection to its presentation in court.